ANALYSIS OF SOYBEAN INVENTORY CONTROL AS RAW MATERIAL FOR KIZZ CRUNCHY TEMPE CHIPS - Annisa Agustina; Pandi Pardian; Yayat Sukayat (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
Inventory control of raw materials is very important at Zanada Tempe House so that soybeans can always be available without the need for additional inventory costs due to excess orders with an irregular schedule. Soybean raw materials that will be processed by Zanada Tempe House are only ordered based on estimated production needs, but have not implemented a certain inventory control model to maintain production success so that it remains economical. This study aims to determine the performance of the production process and control of soybean inventory as raw material for economical